14-fold increased prevalence of rare glucokinase gene variant carriers in unselected Danish patients with newly diagnosed type 2 diabetes. (December 2022) - Gjesing, Anette P.; Engelbrechtsen, Line; Cathrine B. Thuesen, Anne; Have, Christian T.; Hollensted, Mette; Grarup, Niels; Linneberg, Allan; Steen Nielsen, Jens; Christensen, Lotte B.; Thomsen, Reimar W.; Johansson, Kristoffer E.; Cagiada, Matteo; et al.
Abstract: Aims: Rare variants in the glucokinase gene ( GCK ) cause Maturity-Onset Diabetes of the Young (MODY2/ GCK -MODY). We investigated the prevalence of GCK variants, phenotypic characteristics, micro- and macrovascular disease at baseline and follow-up, and treatment among individuals with and without pathogenic GCK variants. Methods: This is a cross-sectional study in a population-based cohort of 5, 433 individuals without diabetes (Inter99 cohort) and in 2, 855 patients with a new clinical diagnosis of type 2 diabetes (DD2 cohort) with sequencing of GCK . Phenotypic characteristics, presence of micro- and macrovascular disease and treatment information were available for patients in the DD2 cohort at baseline and after an average follow-up of 7.4 years. Results: Twenty-two carriers of potentially deleterious GCK variants were found among patients with type 2 diabetes compared to three among 5, 433 nondiabetic individuals [OR = 14.1 (95 % CI 4.2; 47.0), p = 8.9*10 -6 ]. Patients with type 2 diabetes carrying GCK variants had significantly lower waist circumference, hip circumference and BMI, compared to non-carriers. Three GCK variant carriers with diabetes had microvascular complications during follow-up. Conclusions: Approximately 0.8% of Danish patients with newly diagnosed type 2 diabetes carry non-synonymous variants in GCK and resemble patients with GCK -MODY. Glucose-lowering treatment cessation should be considered in this subset of diabetes patients.